Disrupted interactions among the hippocampal, dorsal attention, and central‐executive networks in amnestic mild cognitive impairment - Chand, Ganesh B. (Hum Brain Mapp, 2018)
Neuroimaging investigations consistently demonstrate that the neural processes involve complex interactions between the large‐scale networks. Among those networks, the dorsal attention network (DAN) and the central‐executive network (CEN) have been previously shown to exhibit anti‐correlated activity with the default‐mode network (DMN) in cognitively normal people. In amnestic mild cognitive impairment (MCI) and Alzheimer's disease, the hippocampal network (HCN)—a key memory processing system—and its interactions with other networks have gathered central interest. The current study aims to evaluate the patterns of functional architectures of the HCN with the three networks—DAN, CEN, and DMN—in amnestic MCI and normal controls (NC) to test the hypothesis that the interactions of HCN with other networks alter in MCI. We recorded the resting state functional MRI, assessed patterns of functional architectures between the four networks using dynamical causal modeling, and compared between NC and MCI. Our analysis showed that the DAN modulates the activity between the HCN and the DMN in both MCI and NC. We further uncovered that the DAN modulates the activity between the HCN and the CEN in NC, but such modulation is impaired in MCI. We found an association between impaired modulation and Montreal cognitive assessment (R = 0.349). Overall, our findings provide important insight in understanding the neuroimaging signature of amnestic MCI and/or Alzheimer's disease.